2007
DOI: 10.1016/j.specom.2007.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Towards capturing fine phonetic variation in speech using articulatory features

Abstract: The ultimate goal of our research is to develop a computational model of human speech recognition that is able to capture the effects of fine-grained acoustic variation on speech recognition behaviour. As part of this work we are investigating automatic feature classifiers that are able to create reliable and accurate transcriptions of the articulatory behaviour encoded in the acoustic speech signal. In the experiments reported here, we analysed the classification results from support vector machines (SVMs) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 18 publications
0
43
0
Order By: Relevance
“…Also King et al (2007) mentions SVMs as a powerful classification technique for binary tasks. Then, Scharenborg et al (2007) showed that SVMs even compare favorably to ANNs on the task of multi-level articulatory-acoustic feature classification, which is also the task at hand in the current work. We therefore use SVMs for our investigations.…”
Section: Support Vector Machines (Svms)mentioning
confidence: 66%
See 4 more Smart Citations
“…Also King et al (2007) mentions SVMs as a powerful classification technique for binary tasks. Then, Scharenborg et al (2007) showed that SVMs even compare favorably to ANNs on the task of multi-level articulatory-acoustic feature classification, which is also the task at hand in the current work. We therefore use SVMs for our investigations.…”
Section: Support Vector Machines (Svms)mentioning
confidence: 66%
“…In one line of research, exemplified by Frankel et al (2007b), King and Taylor (2000), Manjunath and Sreenivasa Rao (2016) and Scharenborg et al (2007), attempts are made to cover a full set of features with a single multi-value classifier (with seven classes). In the second line, exemplified by Niyogi et al (1999), Pruthi and Espy-Wilson (2007), and Schutte and Glass (2005), 1 3 research concentrates on finding an optimal set of acoustic parameters for building a detector for one specific manner feature for, e.g., vowel nasalization (e.g., Pruthi and EspyWilson 2007), nasal manner (e.g., Chen 2000; Pruthi and Espy-Wilson 2004), or stops (e.g., Abdelatti Ali et al 2001;Niyogi et al 1999).…”
Section: Acoustic Parameters For Manner Classificationmentioning
confidence: 99%
See 3 more Smart Citations